The Role of Ulama in the Application of Islamic Syariah in Aceh: A Study of Aceh Ulama Council’s Fatwa on Apostasies and Heresies (UINSI Samarinda, 2018)
This article examines the role of ulama in the implementation of Sharia in Aceh by focusing on the study of their fatwa concerning apostasies and heresy. Since the time of the Aceh Sultanate, the role of the ulama has been prominent as the royal judges who applied sharia due to the status Aceh as the region that embraces Sunni Islam as the official schools of jurisprudence and theology. This situation continues in the period of independence and it has legally been further strengthened in the post-Soeharto regime (reformation era) by the special autonomy status granted to Aceh that includes the right to implement sharia in full. Based on the special autonomy, the council of ulama in Aceh, known as Majelis Permusyawaratan Ulama (the Consultative Assembly of Ulama) or MPU) is officially instuted as the government partner and vested with the authority to issue religious edicts (fatwa) and give considerations regarding the problems of governance, development, community development, and Islamic economy to the government. With regards to Islamic theology, the MPU has the authority to determine the orthodoxy of a religious group by issuing fatwa. As studied, there are fourteen fatwa issued by the MPU on sects and religious movements flourished in Aceh which are deemed to be deviating from Islamic orthodoxy; those include Shiah, Millata Abraham, and Gafatar. From in-depth studies of the fatwa, this article reveals that the influential role of ulama in Aceh in the life of society and government comes from three legitimations, namely; history, legal, and social. This thus has made the society and government feel bound by the MPU fatwa on apostasies and heresies which prompt the Aceh government to ban the groups despite freedom of religion guaranteed by the constitution. This condition is theoretically appealing because, as far as the legal system of Indonesia is a concern, obeying a fatwa is a matter moral compliance instead of legal compliance.Keywords: Aceh, Islamic Sharia, Ulama Council’s Fatwa on Apostasies and Heresies